2021
DOI: 10.1016/j.dhjo.2021.101166
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity of people with disabilities who were Medicare beneficiaries during the COVID-19 pandemic

Abstract: Background During the COVID-19 pandemic, 54 million people in the United States were food insecure (2020). People with disabilities (PWD) who were Medicare beneficiaries were especially vulnerable to food insecurity prior to the pandemic. Objective The aim of this study was to explore COVID-19 pandemic food insecurity among PWD who were Medicare beneficiaries. Methods We conducted a secondary analysis of the United States Census Bureau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Although many reported serious negative impacts, at the time of this study, respondents appeared to have been spared other significant, if not life threatening, difficulties experienced by other people with disabilities. For example, while others reported food insecurities during the pandemic [41,42], none of our respondents identified food scarcity as a problem. Since our sample of women had the resources to participate in an online study, perhaps they also had the financial advantages to secure food.…”
Section: Discussioncontrasting
confidence: 74%
“…Although many reported serious negative impacts, at the time of this study, respondents appeared to have been spared other significant, if not life threatening, difficulties experienced by other people with disabilities. For example, while others reported food insecurities during the pandemic [41,42], none of our respondents identified food scarcity as a problem. Since our sample of women had the resources to participate in an online study, perhaps they also had the financial advantages to secure food.…”
Section: Discussioncontrasting
confidence: 74%
“…Our study suggests almost half of Medicare beneficiaries with disabilities had symptoms of generalized anxiety disorder and more than one-third major depressive disorder during the pandemic. Research indicates Medicare beneficiaries with disabilities faced many of the same issues and challenges other populations did during the pandemic (ANCOR Foundation & United Cerebral Palsy, 2021; Embregts et al, 2020; Friedman, 2021; Keppler, 2020; Meyersohn, 2020; Pettinicchio et al, 2021; Pinilla-Roncancio & Alkire, 2021; Pottie & Sumarah, 2004; Pulrang, 2020a; Simplican et al, 2015); however, they also did so while grappling with ableism, and the stress, trauma, and deadly consequences that come with it (Abberley, 1987; Andrews et al, 2019; Autistic Self Advocacy Network, 2020; Barnes, 1997; Bogart & Dunn, 2019; Boyle et al, 2020; Bradley, 2020; Chakraborty, 2021; Dunn, 2019; Friedman, 2019; Gathright, 2020; Kumari-Campbell, 2009; Li, 2020; Oakley et al, 2020; Pulrang, 2020a, 2020b; Shakespeare, 1996; Trent, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, people with disabilities tend to experience more severe levels of food insecurity than those who are not disabled (Coleman-Jensen & Nord, 2013). For example, Friedman (2021) found that 55.7% of people with disabilities who were Medicare beneficiaries did not have enough of the foods they wanted to eat during the pandemic, mostly because they were unable to afford them (56.9%), stores did not carry them (31.4%), and they feared going out (30.0%).…”
mentioning
confidence: 99%